PEMBUATAN BIOETANOL MELALUI FERMENTASI NIRA TEBU (Saccharum officinarum) MENGGUNAKAN Saccharomyces cerevisiae DENGAN PENAMBAHAN VITAMIN B KOMPLEKS SEBAGAI NUTRISI FERMENTASI - Wahyu Budi Utama; Rudi Kartika; Erwin - (JURNAL KIMIA MULAWARMAN, 2016)
Bioethanol is alternative energy produced from the fermentation of carbohydrates like sugar cane juice. The fermentation process is influenced by several factors like nutrition of fermentation. This research to determine the addition weigh (g) of vitamin B complex gr and time of fermentation as theoptimumconditions of fermentaced toproduceethanol with high concentrations. Sugar cane juice as raw material fermented using Saccharomyces cereviceaea with variation additional of vitamin B complex are 0%; 0.1%; 0.2%; and 0.3% (w/v) sugar cane juice fermented during time of fermentation with the variation are 6 day, 7 day and 8 day. Purification of bioethanol by process of distillation.Alcohol content analysis using gas chromatography. The results showed optimumconditions of fermentaced are addition of Vitamin B complex is 0.1% (w/v) and time of fermentation is 7 days to produced ethanol 30.177%.